Changes of the salivary and serum proteome in canine hypothyroidism - González-Aróstegui, Luis G.; Muñoz Prieto, Alberto; Rubio, C. P.; Cerón, J. J.; Bernal, L.; Rubić, I.; Mrljak, V.; Tvarijonaviciute, A. (Domestic animal endocrinology, 2024)
In this study, changes in salivary and serum proteome of dogs with hypothyroidism were studied using tandem mass tags (TMT) labelling and liquid chromatography-mass spectrometry (LC-MS/MS). Saliva and serum proteome from 10 dogs with hypothyroidism were compared with 10 healthy dogs. In saliva, a total of seven proteins showed significant changes between the two groups, being six downregulated and one upregulated, meanwhile, in serum, a total of six proteins showed significant changes, being five downregulated and one upregulated. The altered proteins reflected metabolic and immunologic changes, as well as, skin and coagulation alterations, and these proteins were not affected by gender. One of the proteins that were downregulated in saliva, lactate dehydrognease (LDH), was measured by a spectrophotometric assay in saliva samples from 42 dogs with hypothyroidism, 42 dogs with non-thyroid diseases and 46 healthy dogs. The activity of LDH was lower in the saliva of hypothyroid dogs when compared to non-thyroid diseased dogs and healthy controls. This study indicates that canine hypothyroidism can produce changes in the proteome of saliva and serum. These two sample types showed different variations in their proteins reflecting physiopathological changes that occur in this disease, mainly related to the immune system, metabolism, skin and coagulation. In addition, some of the proteins identified in this study, specially LDH in saliva, should be further explored as potential biomarkers of canine hypothyroidism.
Online verfügbar: 2. November 2023, Artikelversion: 17. November 2023
Gesehen am 23.01.2024